2023
DOI: 10.3390/polym15081918
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of FeOOH-Loaded Aminated Polyacrylonitrile Fiber for Simultaneous Removal of Phenylphosphonic Acid and Phosphate from Aqueous Solution

Abstract: Phosphorus is one of the important metabolic elements for living organisms, but excess phosphorus in water can lead to eutrophication. At present, the removal of phosphorus in water bodies mainly focuses on inorganic phosphorus, while there is still a lack of research on the removal of organic phosphorus (OP). Therefore, the degradation of OP and synchronous recovery of the produced inorganic phosphorus has important significance for the reuse of OP resources and the prevention of water eutrophication. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…It was found that the adsorption reached the equilibrium status within 60 min for CNC@PPy. According to the fitting of adsorption kinetics model in Figure 3 b, all adsorbent materials met the pseudo-second-order model [ 14 , 17 , 18 , 19 ]. The adsorption speed was the fastest, within 40 min, and the adsorption equilibrium could be reached.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that the adsorption reached the equilibrium status within 60 min for CNC@PPy. According to the fitting of adsorption kinetics model in Figure 3 b, all adsorbent materials met the pseudo-second-order model [ 14 , 17 , 18 , 19 ]. The adsorption speed was the fastest, within 40 min, and the adsorption equilibrium could be reached.…”
Section: Resultsmentioning
confidence: 99%
“…According to the fitted experimental data, the adsorption of Hg(II) by this product was consistent with the Freundlich adsorption isotherm model. This indicates that the adsorption of Hg(II) by CNC/PPy adsorbent is a single molecular layer adsorption process and a surface adsorption process [ 17 , 18 , 19 ]. The pseudo-second-order model with R 2 = 0.948 ( Figure 3 d) better represented the adsorption process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations